Memory of Khiva - Xo’janiyozov Shokir Rustamovich; Karimova Ro’zika Baxrom qizi. (Genius Journals, 2023)
This article defines the great contribution of representatives of the Kungirat dynasty, who carried out construction work on the construction of cultural-heritage objects of the city of Khiva, including the components of the Ichan Kala ensemble (mausoleum, mosque, madrasa, palace, towers) in introducing our national architectural art to the world. Also, the construction history and current functions of Muhammad Amin Khan madrasa, which is considered the largest madrasa of Ichan Qala, are explained in detail. The given information and opinions are based on facts
Keywords: Ichan Kala; madrasa; minaret